Lipid Droplet, a Key Player in Host-Parasite Interactions - Vallochi, Adriana Lima; Teixeira, Livia; Oliveira, Karina da Silva; Maya-Monteiro, Clarissa Menezes; Bozza, Patricia T. (Frontiers in Immunology, 2018)
Lipid droplets (lipid bodies, LD) are dynamic organelles that have important roles in regulating lipid metabolism, energy homeostasis, cell signaling, membrane trafficking and inflammation. Lipid droplet biogenesis, composition and functions are highly regulated and may vary according to the stimuli, cell type, activation state and inflammatory environment. Increased cytoplasmic lipid droplets are frequently observed in leukocytes and other cells in a number of infectious diseases. Accumulating evidence reveal lipid droplets participation in fundamental mechanisms of host-pathogen interactions, including cell signaling and immunity. Lipid droplets are sources of eicosanoid production, and may participate in different aspects of innate signaling, and antigen presentation. In addition, intracellular pathogens evolved mechanisms to subvert host metabolism and may use host lipid droplets, as ways of immune evasion and nutrients source. Here we review mechanisms of lipid droplets biogenesis and their contributions to the infection progress, and discuss the latest discoveries on mechanisms and pathways involving lipid droplets roles as regulators of the immune response to protozoan infection.